Nosology of genetic skeletal disorders: 2023 revision - Sheila Unger; Carlos R. Ferreira; Geert Mortier; Houda Ali; Débora Romeo Bertola; Alistair Calder; Daniel H. Cohn; Valérie Cormier‐Daire; Katta M. Girisha; Christine M Hall; Deborah Krakow; Outi Mäkitie; et al. (2023)
Abstract The “Nosology of genetic skeletal disorders” has undergone its 11th revision and now contains 771 entries associated with 552 genes reflecting advances in molecular delineation of new disorders thanks to advances in DNA sequencing technology. The most significant change as compared to previous versions is the adoption of the dyadic naming system, systematically associating a phenotypic entity with the gene it arises from. We consider this a significant step forward as dyadic naming is more informative and less prone to errors than the traditional use of list numberings and eponyms. Despite the adoption of dyadic naming, efforts have been made to maintain strong ties to the MIM catalog and its historical data. As with the previous versions, the list of disorders and genes in the Nosology may be useful in considering the differential diagnosis in the clinic, directing bioinformatic analysis of next‐generation sequencing results, and providing a basis for novel advances in biology and medicine.